1994
DOI: 10.1002/gcc.2870090105
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 7: A potential cytogenetic marker of human prostate cancer progression

Abstract: We used the fluorescence in situ hybridization (FISH) method to show that chromosome 7 trisomy is associated with the progression of human prostate cancer. Thirty-six specimens including 15 primary prostate carcinomas, 16 metastatic lesions, and 5 normal prostate tissues, as well as 2 prostate carcinoma cell lines of different tumorigenic potential, were examined for chromosome 7 aneuploidy. Our results showed that the androgen-unresponsive tumorigenic cell line PC-3 exhibited a significantly higher ratio of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 22 publications
(20 reference statements)
0
50
0
Order By: Relevance
“…In particular, losses of heterozygosity at chromosomes 8p, 10q, 13q, and 17p are frequent events, and losses of 6q, 7q, 16q, and 18q have also been reported, although they are not as well characterized (Latil et al 1994;Zenklusen et al 1994;Takahashi et al 1995;Cooney et al 1996a;Cunningham et al 1996;Elo et al 1997;Latil et al 1997;Saric et al 1999). In addition, although chromosome gains appear to be less frequent than chromosome losses, gains at 8q and 7 are fairly common (Alcaraz et al 1994;Bandyk et al 1994;Van Den Berg et al 1995).…”
Section: A Pathway For Prostate Cancer Initiation and Progression: Anmentioning
confidence: 99%
“…In particular, losses of heterozygosity at chromosomes 8p, 10q, 13q, and 17p are frequent events, and losses of 6q, 7q, 16q, and 18q have also been reported, although they are not as well characterized (Latil et al 1994;Zenklusen et al 1994;Takahashi et al 1995;Cooney et al 1996a;Cunningham et al 1996;Elo et al 1997;Latil et al 1997;Saric et al 1999). In addition, although chromosome gains appear to be less frequent than chromosome losses, gains at 8q and 7 are fairly common (Alcaraz et al 1994;Bandyk et al 1994;Van Den Berg et al 1995).…”
Section: A Pathway For Prostate Cancer Initiation and Progression: Anmentioning
confidence: 99%
“…Trisomy 7, which has been described as a common anomaly in solid malignant tumours (Weaver et al, 1988;Belge et al, 1994), was found in four (14%) cases (Case 3,16,23,27). In a previous study, trisomy 7 was reported to serve as a novel marker for human prostate cancer progression (Bandyk et al, 1994), and several authors (Collard et al, 1987;Trent et al, 1990) (Arps et al, 1993), and that the most common clonal numerical aberration was loss of Y in 5 of 62 (8%) prostatic adenocarcinomas . A previous report (Aly et al, 1994) combining conventional cytogenetic analysis and FISH of short-term culture of benign prostatic hyperplasia showed loss of chromosome Y to be the most common chromosomal change.…”
Section: Discussionmentioning
confidence: 96%
“…Trisomy 7 is, however, increased in epithelial tumor cells of colon carcinoma 42 and is considered to correlate with tumor progression in human prostate cancer. 43 Trisomy 7, and a stepwise increase of non-random trisomies, is also a characteristic abnormality in benign thyroid tumors. 44 Loss of the Y chromosome and trisomy 7 were the most common abnormalities noted in benign prostatic hyperplasia, 45 although the authors point out the possibility that the trisomic cells may be infiltrating lymphocytes, which may have trisomy 7.…”
Section: Discussionmentioning
confidence: 99%